Cross-sectional assessment of Angiostrongylus cantonensis transmission risk mediated by invasive apple snails in Jiangsu province of China - Zhang, Qiang; Mao, Fanzhen; Ni, Bixian; Zhang, Jiayao; Tang, Feng; Gong, Xinyi; Liu, Yaobao (PLOS Neglected Tropical Diseases, 2025)
Author summary In this study, we investigated the risk of human infection with the rat lungworm, Angiostrongylus cantonensis, which can cause severe meningitis. This parasite is often spread through invasive apple snails, which are now widespread in Jiangsu Province, China. We combined field surveys of snails with a public questionnaire to understand both ecological and behavioral risks. Although we did not find any infected snails in the wild or in local markets, our survey revealed important gaps in public health practices. For example, many people do not separate utensils for raw and cooked food, and few use our reporting app for snail sightings. We also observed that older individuals and those with lower levels of education demonstrated lower awareness and exhibited less effective preventive habits. Our findings show that even without current detection of the parasite, the potential for outbreak remains because of widespread snails and unsafe behaviors. We recommend targeted health education, especially for high-risk groups, and continued monitoring to prevent future infections. This integrated approach will help protect both public health and local ecosystems.